iTRAQ-based comparative proteomic analysis of cells infected with Eimeria tenella sporozoites - Zhao Zongping; Zhao Qiping; Zhu Shunhai; Huang Bing; Lv Ling; Chen Ting; Yan Ming; Han Hongyu; Dong Hui (Parasite, 2019)
Eimeria tenella is an obligate intracellular parasite that actively invades cecal epithelial cells of chickens. When E. tenella infects a host cell, the host produces a corresponding change to deal with damage caused by this infection. To date, our knowledge on the mechanism of how the host cell responds to E. tenella infection is highly limited at both the molecular and cellular levels. In this study, isobaric tags for relative and absolute quantitation (iTRAQ) coupled with LC-MS/MS was used to screen the differentially expressed proteins (DEPs) in BHK-21 cells infected with E. tenella sporozoites for 24 h post infection. In total, 6139 non-redundant distinct proteins were identified and 195 of these were found to have a fold change ratio ≥1.3 or ≤0.7 and p < 0.05, including 151 up-regulated proteins and 44 down-regulated proteins. The reliability of the proteomic data was further validated with qPCR and western blot. Gene Ontology enrichment indicated that the up-regulated DEPs were mainly involved in binding and catalytic activity, whereas the down-regulated DEPs were catalytic activity and molecular function regulators. Furthermore, KEGG pathway analysis showed that the DEPs participated in the PI3K-Akt, chemokine, Ras, Wnt, and p53 signaling pathways and so on, and the up-regulated and down-regulated DEPs mainly related to the ribosome and mRNA surveillance pathway, respectively. The data in this study provide an important basis to further analyze E. tenella host cell interactions.